The Loan Puzzle. A Study of Loans to Different Groups in the USA. - Gianluca Cafiso (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study loans from banking and non-banking lenders to different groups of borrowers in order to unveil significant differences on how those respond to a shock and evaluate possible alternative explanations for such differences. The objective is to gain insights useful to explain the loan puzzle: the unexpected increase of loans to firms in case of a monetary tightening. The analysis is based on a vector autoregression, estimated using Bayesian techniques, and has as object the US economy.
Keywords: E44; E51; G20; G21; C11; 330; loan puzzle; households; corporate businesses; non-corporate businesses; VAR; Bayesian estimation